Hur långt får domaren gå? Rättsliga ramar för förlikning i dispositiva tvistemål. - Benjegård,Elmer (2025)
The court is under a mandatory obligation to promote settlement according to Chapter 42, Section 17 of Rättegångsbalken. However, the statutory provis ion largely lacks guidance on what it entails for a judge to “promote” settle ment. The purpose of this thesis is to clarify the court’s duties and discret ionary powers in settlement efforts within dispositive civil cases. This is done by addressing three sub-questions: Under what circumstances should the court seek to reconcile disputing parties? How should the judge proceed in order to facilitate a settlement? At what point do the judge’s efforts to encou rage settlement go too far and risk compromising impartiality? The analysis primarily draws on legal doctrine and preparatory works to answer these questions. Finally, the findings are discussed and evaluated. The conclusion is that Swedish judges are granted considerable discretion by both legal scho lars and the legislature in their efforts to settle disputes between parties.
Keywords: Processrätt; Förlikning